Zombie firms in China's coal mining sector: Identification, transition determinants and policy implications. (August 2019) - Dai, Xiaoyong; Qiao, Xiaole; Song, Lin
Abstract: This paper uses a modified identification method to identify zombie firms from a large sample of coal mining companies in China. It analyzes the prevalence of zombie firms over time and their distribution across different regions and ownership types. It also investigates the causes of the emergence of zombies and evaluates the effectiveness of various restructuring measures for resolving zombie firms. The results indicate that government interventions and subsidized bank credit are important causes of zombie firms, and continuous financial support from the government or banks does not contribute to the recovery of zombie firms. While reductions in labor costs, ownership reforms, and deleveraging can effectively resolve zombie firms, the injection or sale of assets has an ambiguous impact on the recovery of zombie firms. This study contributes to an understanding of the causes of the emergence of zombie firms and provides some policy implications for tackling zombie firms in China's coal sector. Highlights: We identify zombie firms in China's coal mining sector. We apply a modified identification approach to coal mining companies. We analyze the distribution of identified zombie firms. We investigate the causes of the emergence of zombie firms. We evaluate the effectiveness of restructuring measures of resolving zombie firms.